Response of Groundnut Genotypes to Photosynthetically Active Radiation - Gajjar, R B; Shekh, A M; Patel, N M (Annals of Arid Zone, 2016)
The causes of high yieldpotential of groundnut (Arachish hypogaea L.) genotype Robut 33-1in comparisonto GG-2(the releasedvariety)duringsummerseasonwere assessed under experimentallycreated varyingenvironmentsusing meteorologicalparameters. The genotype Robut 33-1 had higher PAR conversionuse efficiency(CUE) than GG-2 at all the growth stages studied. The relation betweenPAR absorption coefficient(Y), and days after sowing (D) for Robut 33-1 was : Y = -0.647 + ,0.010 ; 0.0000570 D2 and for GG-2 it was : Y = -1.016 + 0.0296830 - 0.0001250, With R2 > 0.86. The rate of dry matter production was linear over the intercepted PAR (R2 > 0.88).The CUE (dlY matter produced per unit of intercepted PAR), by linear regression technique was 1.542 g Mr-1 in Robut 33-1 and 1.067g Mr1 in GG-2. The results revealed that PAR and CUE. could be utilized in selection programme for high yield potential.